Gambaran Resiliensi Single Mother Setelah Perceraian di Desa Kecamatan Perhentian Raja - Nidya Larasati; Ahmad Hidayat; Rahmad Muliadi (UIR Press, 2022)
Resilience is very important in helping single mothers to overcome the difficulties encountered on a daily basis. This study aims to determine the picture of single mother resilience after divorce and the factors that affect single moter resilience after divorce. The subjects in this study were two single mothers in Pantai Raja Village, Perhentian Raja District, Kampar Regency. The research method used is a descriptive qualitative research method with a case study approach and the data collection used is interviews and observations. The results of this study showed that the two subjects of the study had good resilience, where after divorce each subject had the ability of a variety of resilience processes. This is in accordance with the ability of both subjects to overcome a problem and the subject's ability to be able to adapt and socialize with the surrounding environment.